Análise sobre a divulgação de quantitativos de fraude corporativa e corrupção: relatórios de empresas ISE B3 - Santos, César Augusto da Silva (2024)
The objective of this work was to evaluate whether there is transparency in the disclosure of investigations of complaints and metrics that allow comparability, based on information made available in sustainability and/or integrated reports, by companies listed in B3's ISE portfolio. To this end, documents and public data from 69 companies in the ISE portfolio were analyzed to verify how these institutions disclose information about corporate fraud and corruption, whether they report their outcomes and whether they have indicators that allow comparability among stakeholders. The results indicate that, although companies adopt ESG and corporate governance practices, with an approach to ethical issues and the establishment of integrity controls, including Reporting Channels, as well as seeking alignment with SDG 16 in the fight against corruption, in Regarding training, it was observed that the focus of institutions is to benefit from possible mitigations in relation to national and international legislation, such as the Brazilian Anti-Corruption Law (Law 12,846/13) and the American Anti-Corruption Law (FCPA). The disclosure of cases of corporate fraud and corruption has a very discreet tendency towards more transparent and ethical practices, as in valid cases the types, motivations, causes and agents are not disclosed, nor is there a standard of disclosure. In this sense, the work contributes to a reflection on the part of managers and regulators regarding the need to encourage the creation of comparable models and metrics for disclosing specific information about cases of corporate fraud and corruption. Additionally, the research contributes to academia filling the existing gap in the literature on this topic